Choosing the Wrong Major: what is the profile of students who feel they have chosen the wrong major ? - Diana, Diana; Guntur, Irene; Roebianto, Adiyo; Christy, Christy (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This study aims to identify the main factors in the selection of majors in college. There were 1283 participants consisting of first, second, and third year students from various universities in Indonesia, both public and private. The research approach was non-experimental quantitative using descriptive and inferential statistics. The results showed that almost 30% of students felt that they chose the wrong major. Those who felt they chose the wrong major had lower knowledge domain (μ = 42.67; t = 20.376, p < 0.05) and help-seeking behavior (μ = 47.89; t = 5.336, p < 0.05) compared to those who felt they chose the right major. Based on the type of university, 274 students from public universities (72.29%) and 105 students from private universities (27.71%). The conclusion was that students who felt they had the wrong major did not have adequate Self Knowledge and Occupational Knowledge. Their need to seek help has not been accompanied by sufficient knowledge about themselves and their intended careers, hence students need to be proactive in gaining knowledge from credible sources. This study mapped the factors that influenced major selection and thus guidance on major selection since high school should be considered.